Immunization with different recombinant West Nile virus envelope proteins induces varying levels of serological cross-reactivity and protection from infection - Weiß, Rebecca; Issmail, Leila; Rockstroh, Alexandra; Grunwald, Thomas; Fertey, Jasmin; Ulbert, Sebastian (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction West Nile Virus (WNV) is a zoonotic flavivirus transmitted by mosquitoes. Especially in the elderly or in immunocompromised individuals an infection with WNV can lead to severe neurological symptoms. To date, no human vaccine against WNV is available. The Envelope (E) protein, located at the surface of flaviviruses, is involved in the invasion into host cells and is the major target for neutralizing antibodies and therefore central to vaccine development. Due to their close genetic and structural relationship, flaviviruses share highly conserved epitopes, such as the fusion loop domain (FL) in the E protein, that are recognized by cross-reactive antibodies. These antibodies can lead to enhancement of infection with heterologous flaviviruses, which is a major concern for potential vaccines in areas with co-circulation of different flaviviruses, e.g. Dengue or Zika viruses. Material To reduce the potential of inducing cross-reactive antibodies, we performed an immunization study in mice using WNV E proteins with either wild type sequence or a mutated FL, and WNV E domain III which does not contain the FL at all. Results and discussion Our data show that all antigens induce high levels of WNV-binding antibodies. However, the level of protection against WNV varied, with the wildtype E protein inducing full, the other antigens only partial protection. On the other hand, serological cross-reactivity to heterologous flaviviruses was significantly reduced after immunization with the mutated E protein or domain III as compared to the wild type version. These results have indications for choosing antigens with the optimal specificity and efficacy in WNV vaccine development.